(untitled) (Analysis in Theory and Applications, 2018)
In this paper, we have investigated second Hankel determinants and Fekete-Szegö inequalities for some subclasses of Bi-univalent functions with respect to symmetric and Conjugate points which are subordinate to a shell shaped region in the open unit disc ∆.